Volume 1: Biofuels, Hydrogen, Syngas, and Alternate Fuels; CHP and Hybrid Power and Energy Systems; Concentrating Solar Power; 2016
DOI: 10.1115/es2016-59238
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of a High-Temperature Falling Particle Receiver

Abstract: This paper evaluates the on-sun performance of a 1 MW falling particle receiver. Two particle receiver designs were investigated: obstructed flow particle receiver vs. free-falling particle receiver. The intent of the tests was to investigate the impact of particle mass flow rate, irradiance, and particle temperature on the particle temperature rise and thermal efficiency of the receiver for each design. Results indicate that the obstructed flow design increased the residence time of the particles in the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The simulated system is a simplified subdomain of a complete FPR and the surrounding air space. The system is modeled after an existing, north-facing 1 MW th FPR at the National Solar Thermal Test Facility (NSTTF) at Sandia National Laboratories [30]. The analyzed system includes a hood over the aperture that is not present in the existing receiver.…”
Section: Computational Modelmentioning
confidence: 99%
“…The simulated system is a simplified subdomain of a complete FPR and the surrounding air space. The system is modeled after an existing, north-facing 1 MW th FPR at the National Solar Thermal Test Facility (NSTTF) at Sandia National Laboratories [30]. The analyzed system includes a hood over the aperture that is not present in the existing receiver.…”
Section: Computational Modelmentioning
confidence: 99%
“…In recent years, many research institutions have developed solar receiver models and carried out experiments [2]. Researchers from the Sandia National Laboratory (SNL) working on direct radiation solid particle solar receivers (SPSR) conducted two series of tests related with the area of exposure to solar radiation, in free-falling SPSR systems in 2008 and 2016 [3]. Reducing the designed opening area from 4.5 m 2 to 1 m 2 greatly reduced the convective heat loss and increased the thermal efficiency from 33-53% to 50-80%.…”
Section: Introductionmentioning
confidence: 99%
“…The falling particle receiver appears well-suited for scalability ranging from 10 -100 MW e power-tower systems. Previous studies have considered alternative particle receiver designs including freefalling [18], obstructed flow [24,25], centrifugal [20,21,26,27], flow in tubes with or without fluidization [15,22,23,[28][29][30][31], multi-pass recirculation [9,17] north-or south-facing [6,11], and face-down configurations [32]. In general, these particle receivers can be categorized as either direct or indirect particle heating receivers.…”
Section: Introductionmentioning
confidence: 99%
“…Those tests achieved 1.2 m ~50% thermal efficiency, and the maximum particle temperature increase was ~250°C. More recently, Ho et al have performed on-sun tests of a 1 MW th continuously recirculating particle receiver with bulk particle outlet temperatures reaching over 700 °C, and thermal efficiencies from ~50% -80% [24,25] (Figure 3). Results showed that the particle temperature rise and thermal efficiency were dependent on particle mass flow rate and irradiance.…”
Section: Introductionmentioning
confidence: 99%